2022
DOI: 10.1177/20363613221148547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and paraclinical features, outcome, and prognosis of ovarian granulosa cell tumor: A retrospective study of 28 Vietnamese women

Abstract: Background: Granulosa cell tumor of the ovary is a rare disease and presents with two clinically and molecularly distinct subtypes: the juvenile and the adult type. GCT is considered as a malignant tumor with an indolent course and a tendency toward late recurrence. Purpose: To assess the clinical and paraclinical features, treatment findings, survival outcomes, and explored the prognostic factors in the granulosa cell tumor. Methods: The current study was conducted on 28 GCT patients who had surgical operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Oseledchyk et al 32 and Linsong et al 51 found that the 5-year DFS in the CT group was significantly lower than that in the non-CT group. Le et al, 38 Mangili et al, 36 and Park et al 31 found that the 5-year DFS in the CT group was lower than that in the non-CT group without statistical significance. The pooled result suggested that adjuvant CT did not improve the 5-year DFS of AOGCT.…”
Section: Discussionmentioning
confidence: 98%
“…Oseledchyk et al 32 and Linsong et al 51 found that the 5-year DFS in the CT group was significantly lower than that in the non-CT group. Le et al, 38 Mangili et al, 36 and Park et al 31 found that the 5-year DFS in the CT group was lower than that in the non-CT group without statistical significance. The pooled result suggested that adjuvant CT did not improve the 5-year DFS of AOGCT.…”
Section: Discussionmentioning
confidence: 98%